2012
DOI: 10.1063/1.3679155
|View full text |Cite
|
Sign up to set email alerts
|

Horizontally-aligned carbon nanotubes arrays and their interactions with liquid crystal molecules: Physical characteristics and display applications

Abstract: We report on the physical characteristics of horizonthally-grown Single-Walled Carbon Nanotubes (h-al-SWNT) arrays and their potential use as transparent and conducting alignment layer for liquid crystals display devices. Microscopy (SEM and AFM), spectroscopic (Raman) and electrical investigations demonstrate the strong anisotropy of h-al-SWNT arrays. Optical measurements show that h-al-SWNTs are efficient alignment layers for Liquid Crystal (LC) molecules allowing the fabrication of optical wave plates. Inte… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(10 citation statements)
references
References 38 publications
0
10
0
Order By: Relevance
“…The electrical conductivity along the main axis of the tube can typically be several orders of magnitude larger than that in the tube's radial direction. As a consequence, with the assistance of self-assembly CNTLCs, CNT films with specific structures, vertically aligned CNT arrays or horizontally aligned CNT arrays, can be obtained, which will have considerable potential to be used as transparent electrodes [356][357][358][359]. Compared to the traditional ITO electrodes, which are suffering from difficulties such as the brittleness of ITO, the rising cost of indium, and the high vacuum and temperature processing during the production, CNT electrodes have great advantages in terms of their flexibility, low cost, safe fabrication process and special conductivity anisotropy, which make them a good substitute for ITO in the LCD industries [360,361].…”
Section: Lc-aided-assembly and Self-assembly Of Nanomaterialsmentioning
confidence: 99%
“…The electrical conductivity along the main axis of the tube can typically be several orders of magnitude larger than that in the tube's radial direction. As a consequence, with the assistance of self-assembly CNTLCs, CNT films with specific structures, vertically aligned CNT arrays or horizontally aligned CNT arrays, can be obtained, which will have considerable potential to be used as transparent electrodes [356][357][358][359]. Compared to the traditional ITO electrodes, which are suffering from difficulties such as the brittleness of ITO, the rising cost of indium, and the high vacuum and temperature processing during the production, CNT electrodes have great advantages in terms of their flexibility, low cost, safe fabrication process and special conductivity anisotropy, which make them a good substitute for ITO in the LCD industries [360,361].…”
Section: Lc-aided-assembly and Self-assembly Of Nanomaterialsmentioning
confidence: 99%
“…The difficulties of ITO revolve around the rising cost of indium, the brittleness of ITO, as well as the high temperature and vacuum processing used in the production. 31,32,44 While CNT lms have advantages in low cost due to the natural abundance of carbon, exible or solution processed application, amenability to spray and printing process. 31,32,44,105 So they are hopeful to overcome the above mentioned disadvantages and to be the substitute for ITO.…”
Section: Cnt Lms As Electrodesmentioning
confidence: 99%
“…The exploration of relationship between Frank elasticity to nanotubes and the defective properties will contribute to their liquid crystalline formation and the related applications, especially for the combination with LCs in displays. [31][32][33][34][35][36][37][38][39][40][41][42][43][44][45] In the area of liquid crystal display (LCD), combination of CNTs and LCs is expected to demonstrate exceptional novel or surprising properties. On one hand, LC molecular liquid can facilitate large-scale uniform alignment of CNTs along their director even for relatively high concentration.…”
Section: Introductionmentioning
confidence: 99%
“…Molecular dynamics simulations have shown that the mobility 5CB molecules becomes more restricted due to interaction with the CNT surface [120]. The strong interaction between carbon surface and LC molecules was also experimentally confirmed by the spontaneous alignment of nematic liquid crystals on oriented carbon fibers [121] or SWCNTs [122,123].…”
Section: Surface Anchoring and Alignment Of Cntsmentioning
confidence: 92%